LKPD Berbasis Saintifik Menggunakan Model Discovery Learning Terhadap Hasil Belajar Fisika Siswa Kelas XI MAN 2 Padang - Elfiana Lathifa Rahma; Hufri Hufri; Yohandri Yohandri (Universitas Negeri Padang, 2018)
The result of physiscs learning of XI class MIPA students at MAN 2 Padang was not yet fulfilled the expectation, seen in the student score that has not fulfilled the minimum completeness criterion (KKM) that determined. The purpose of this research is to see if there is influence of scientifically based on LKPD using discovery learning model to physics learning result. The type of research used is quasi experiment using randomized control-group only design. Sampling technique using purposive sampling. Sampling of data is limited to two domains of learning result that is knowledge and skill aspect with written test instrument in the from of a multiple choice question on knowledge aspect and performance instrument by using a scoring rubric on skill aspect. The result of the analysis shows that rhe average of experimental class for the learning outcomes in the knowledge and skill aspect is higher than the class control. The result of the analysis show that the average of experimental class fot the learning outcomes is the knowledge and skills aspect is higher than the class control. It can be concluded that the use of scientific-based LKPD using discovery learning model has a significant influence on the student’s physics learning result of XI class MAN 2 Padang.